Scaling behavior in the heart rate variability characteristics with age - Irurzun, Isabel Maria (2018)
In this work we study the characteristics of the heart rate variability (HRV) as a function of age and gender. The analyzed data include previous results reported in the literature. The data obtained in this work expand the range of age studied until now revealing new behaviors not reported before. We analyze some measurements in the time domain, in the frequency domain and nonlinear measurements. We report scaling behaviors and abrupt changes in some measurements. There is also a progressive decrease in the dimensionality of the dynamic system governing the HRV, with the increase in age that is interpreted in terms of autonomic regulation of cardiac activity.